SERAPAN NITROGEN DARI PANGKASAN POHON LEGUM OLEH TANAMAN PANGAN PADA SISTEM BUDIDAYA PAGAR - Y. Nuraini; E. Handayanto (Universitas Tribhuwana Tunggadewi, 2006)
A study to test the recovery of nitrogen released from five legume tree prunings (Calliandra calothyrsus, Peltophorum dasyrrachis, Gliricidia sepium, Leucaena leucocephala, and Flemingia congesta) was carried out in a glasshouse for 7 weeks. Results showed that the amounts of mineral-N in the soil receiving legume tree prunings ranged from 20 mg/kg soil (Peltophorum) to 37 mg/kg soil (Gliricidia). Addition of Gliricidia produced significantly (P